THE USE OF DIARY TO TEACH WRITING RECOUNT TEXT TO EIGHTH GRADERS OF JUNIOR HIGH SCHOOL WR. SOEPRATMAN TANJUNG REDEB, EAST BORNEO (RETAIN, 2017)
THE USE OF DIARY TO TEACH WRITING RECOUNT TEXT TO EIGHTH GRADERS OF JUNIOR HIGH SCHOOL WR. SOEPRATMAN TANJUNG REDEB, EAST BORNEO Elisa Enda Andreys English Department, Faculty of Languages and Arts, State University of Surabaya E-mail: elisaandreys@mhs.unesa.ac.id Dr. H. Aswandi, M.Pd. English Department, Faculty of Languages and Arts, State University of Surabaya E-mail: aswandi@unesa.ac.id Abstrak Menulis adalah salah satu ketrampilan yang harus dikuasai oleh siswa. Menulis merupakan keterampilan yang lebih sulit daripada keterampilan lainnya, sehingga guru harus memikirkn media apa yang dapat digunakan oleh guru untuk membuat menulis menjadi lebih menarik bagi siswa. Salah satu media yang dapat digunakan oleh guru untuk membantu siswa adalah diary. Subjek dalam penelitian ini adalah salah satu guru bahasa Inggris dan siswa kelas VIII SMP WR. Soepratman Tanjung Redeb, Kalimantan Timur. Penelitian ini merupakan penelitian deskriptif kulaitatif. Pengumpulan data dalam penelitian ini diperoleh dari hasil observasi dan hasil angket. Hasil penelitian ini menunjukkan bahwa diary dapat digunakan sebagai media dalam mengajar menulis recount teks. Diary dapat membantu guru untuk mendapatkan ketertarikan siswa dan membantu siswa mengembangkan kemampuan menulis mereka. Kata Kunci: Berbicara, Teks Recount, Diary. Abstract Writing is one of the skills that should be mastered by the students. Writing is the difficult one than other skills, so the teacher have to think about media that can be used by the teacher to make writing become interesting to stuents. One of media that can be used by the teacher is diary. The subject of this study were one of the English teachers and the eighth gradres of Junior High School WR. Soepratman Tanjung Redeb, East Borneo.this is descriptive qualitative research. The data were collected from the result of the observation checklist and the result of questionnaire.The result showed that Diary can be used by the teacher as learning media in teaching writing recount text. Diary can help the teacher to get the students’ interest and help the students to develop their writing ability. Keywords: Writing, Recount Text, Diary.